Mycotic infection prevalence among patients undergoing bronchoalveolar lavage with search of SARS-CoV-2 after two negative nasopharyngeal swabs. (13th September 2021) - Patrucco, Filippo; Airoldi, Chiara; Falaschi, Zeno; Bellan, Mattia; Castello, Luigi Mario; Filippone, Francesco; Matranga, Simone; Masellis, Serena; Smeriglia, Aurora; Solidoro, Paolo; Balbo, Piero Emilio; Gavelli, Francesco
Abstract: The evidence that severe coronavirus disease 2019 (COVID-19) is a risk factor for development of mycotic respiratory infection with an increased mortality is rising. Immunosuppressed are among the most susceptible patients and Aspergillus species is the most feared superinfection. In this study we evaluated mycotic isolation prevalence on bronchoalveolar lavage (BAL) of patients who underwent bronchoscopy in search of severe acute respiratory coronavirus 2 (SARS-CoV-2) RNA. Moreover, we described the clinical characteristics and main outcomes of these patients. We included 118 patients, 35.9% of them were immunosuppressed for different reasons: in 23.7% we isolated SARS-CoV-2 RNA, in 33.1% we identified at least one mycotic agent and both in 15.4%. On BAL we observed in three cases Aspergillus spp, in six cases Pneumocystis and in 32 Candida spp. The prevalence of significant mold infection was 29.3% and 70.7% of cases were false positive or clinically irrelevant infections. In-hospital mortality of patients with fungal infection was 15.3%. The most frequent computed tomography (CT) pattern, evaluated with the Radiological Society of North America consensus statement, among patients with a mycotic pulmonary infection was the atypical one ( p < 0.0001). Mycotic isolation on BAL may be interpreted as an innocent bystander, but its identification could influence the prognosis of patients, especially in those who need invasive investigations during the COVID-19 pandemic; BAL plays a fundamental role in resolving clinical complex cases, especially in immunosuppressed patients independently from radiological features, without limiting its role in ruling out SARS-CoV-2 infection.